Pentecôtisme au Québec: convergence d’imaginaires religieux et rôle des femmes immigrantes - Estela Ferraro, Ferraro (Université du Québec à Montréal, 2010)
Keywords: Femmes

La place des femmes dans le judaïsme: un chapitre distinct? - Zylberberg, Sonia (Les communautés juives de Montréal. Histoire et enjeux contemporains, 2010)
Keywords: Femmes; Juifs

Associations de femmes immigrantes à Montréal: participer, appartenir, être reconnues: une voie d'intégration symbolique à la société locale - Normandin, Amélie (Université de Montréal, 2010)
Keywords: Centre Femmes du monde; Femmes

Femmes philanthropes: catholiques, juives et protestantes dans les organisations caritatives au Québec, 1880-1945 - Cohen, Yolande (Presses de l'Université de Montréal, 2010)
Keywords: Femmes; Juifs; Philanthropie; Protestants

'Une terre humaine': Expo 67, Canadian Women, and Chatelaine/Châtelaine - Kröller, Eva-Marie (Expo 67: Not Just a Souvenir, 2010)
Keywords: Femmes

Entrepreneurs in the New Economy: Immigration and Sex Effects in the Montreal Metropolitan Area - Paré, Sylvie; Therasme, Kelogue (Journal of International Entrepreneurship, 2010)
The recent literature on women’s entrepreneurship shows that they are underrepresented in the main stream economy when compared to their male counterparts, a phenomenon typically observed in other urban contexts. Approximately 30% of the entrepreneurs in the Montreal metropolitan area are women, active in a variety of sectors of the general economy. Their underrepresentation is still greater in the new economy, that is, those sectors that are knowledge-based and/or specialized in information technologies and communications. In this article, we examine the place of female entrepreneurs in the larger economy and in the new economy as related to their immigrant and/or ethnic origins. We seek in this paper to establish a comparative analysis of the situation of women entrepreneurs in immigrant-origin groups, focusing our attention on both the presence of women in entrepreneurial positions and the differential impact associated with membership in an immigrant-origin group. Based on data derived from Scott's Directory of 2007, we first determined an operational definition of the new economy and then analyzed the data from the perspective of sex and ethnic/immigrant origin. New economy enterprises represent approximately 12% of businesses in the Montreal metropolitan area, the majority of which are of the knowledge-based variety, and there is a relative, statistically significant absence of women from such enterprises. At the same time, there is a significantly greater presence of women drawn from minority groups, that is, from groups other than the Anglo-Canadian and French-Canadian dominant groups.
Keywords: Femmes; Travail

L'enfantement dans un Québec moderne: générations, mémoires, histoire - Rivard, Andrée (Université Laval, 2010)
Keywords: Enfants; Femmes

Solidarity Economy in Montreal: Women's Activism Creating Alternatives Through the Ethics of Care - Germain, L. Marie-France (Université Concordia, 2010)
Keywords: Femmes; Pauvreté

Maidenly Storytellers: The Narrative Role of Female Allegorical Figures in Two Montreal Monuments - McDonagh, Erin Shavaughn (Université Concordia, 2010)
Keywords: Femmes; Monuments

Babies for the Nation: the Medicalization of Motherhood in Quebec, 1910-1970 - Baillargeon, Denyse (Wilfrid Laurier University Press, 2010)
Keywords: Enfants; Femmes; Médecine

La présence lesbienne dans le théâtre féministe québécois des années 1975-1985 chez Marie-Claire Blais, Pol Pelletier et Jovette Marchessault - Laillou Savona, Jeannelle (Voix et Images, 2010)
Keywords: Femmes; Féminisme; Théâtre

Families, Lovers and their Letters: Italian Postwar Migration to Canada - Cancian, Sonia (Studies in Immigration and Culture, 2010)
Keywords: Famille; Femmes; Italiens

Sri Lankan Women's Career Identity Evolution after Immigration to Montreal, Quebec, Canada - De Silva, Nilmini (Université McGill, 2010)
Keywords: Femmes; Sri Lankais; Travail

Le front domestique à la Fédération nationale Saint-Jean-Baptiste: entre crise de la domesticité et promotion de l'enseignement ménager, 1900-1927 - Charron, Catherine (Histoire sociale / Social History, 2010)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

Le genre d’une migration post-coloniale: de Meknès (Maroc) à Montréal (Québec) - Cohen, Yolande (Genre et Histoire, 2010)
Keywords: Femmes; Féminisme; Historiens; Juifs; Marocains

Les procédés discursifs relatifs à l'engagement civique présents dans La Bonne parole , 1939-1951 - Brisebois, Marilyne (Bulletin d'histoire politique, 2010)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste; Guerre; Travail